2021
DOI: 10.1016/j.forsciint.2021.110755
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem radiologic and pathologic findings in COVID-19: The Toronto experience with pre-hospitalization deaths in the community

Abstract: Over a year after the initial emergence of the disease, the COVID-19 pandemic continues to strain healthcare systems worldwide. The value of feedback and connection between clinical care, public health, and death investigation systems has never been more clear. To this end, knowledge of the radiologic and histopathologic features of fatal COVID-19 is critical for those working with the living and the dead. Most of the medical descriptions of COVID-19 are either focused on clinical in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 21 publications
4
40
0
Order By: Relevance
“…The most common clinical presentation of severe COVID-19 is acute respiratory failure consistent with the acute respiratory distress syndrome (ARDS). Studies have shown diffuse alveolar damage with hyaline membrane formation, pneumocyte activation, microvascular thrombi, lymphocytic inflammation, proteinaceous edema, vascular remodeling via intussusceptive angiogenesis in the presence of microvascular thrombi, fibrosis, chronic inflammation, loose fibrous plugs associated with organizing pneumonia, endothelial injury with vacuolization of the cytoplasm and detachment of cells in small and medium-sized pulmonary arteries, deposition of fibrin and erythrocytes in the alveolar spaces and septa, hemorrhage, and hemosiderin deposition accompanied by complement complex deposition (especially near the alveolar capillaries), as well as alveolar type II (AT2) cell hyperplasia, fibrin exudates, vascular congestion, and mononuclear and multinucleated giant cell alveolar inflammation (with a noted absence of neutrophilic inflammation) in humans with COVID-19 [ 64 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common clinical presentation of severe COVID-19 is acute respiratory failure consistent with the acute respiratory distress syndrome (ARDS). Studies have shown diffuse alveolar damage with hyaline membrane formation, pneumocyte activation, microvascular thrombi, lymphocytic inflammation, proteinaceous edema, vascular remodeling via intussusceptive angiogenesis in the presence of microvascular thrombi, fibrosis, chronic inflammation, loose fibrous plugs associated with organizing pneumonia, endothelial injury with vacuolization of the cytoplasm and detachment of cells in small and medium-sized pulmonary arteries, deposition of fibrin and erythrocytes in the alveolar spaces and septa, hemorrhage, and hemosiderin deposition accompanied by complement complex deposition (especially near the alveolar capillaries), as well as alveolar type II (AT2) cell hyperplasia, fibrin exudates, vascular congestion, and mononuclear and multinucleated giant cell alveolar inflammation (with a noted absence of neutrophilic inflammation) in humans with COVID-19 [ 64 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same study found high levels of the blood enzyme troponin, an indicator of heart damage, in 76% of patients tested, even though heart function appeared to be generally preserved. Furthermore, current evidence demonstrates myocardial inflammation with or without direct cardiomyocyte damage in humans with SARS-CoV-2 infection [ 77 , 78 , 79 , 80 , 94 , 95 , 96 , 97 ]. Myocarditis results from direct heart invasion by the virus itself or more commonly by inflammation caused by cytokine storm, resulting in an enlarged and weakened heart, leading to low blood pressure and fluid deposition in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Their major concern is a small but definite number of cases with initial negative SARS-CoV-2 RT-PCR testing on nasopharyngeal swabs in high-risk individuals, having typical CoVID-19 pneumonitis findings on clinical CT and positive RT PCR on repeat nasopharyngeal testing [17]. To date there has been limited literature published on PMCT findings of CoVID-19 pneumonitis [18][19][20][21], and only 1 study of 5 cases looking specifically at the question of PMCT screening for CoVID-19 disease in unexpected community deaths [22].…”
Section: Discussionmentioning
confidence: 99%
“…Complete consolidation of both lungs (indicative of ARDS) has also been reported in severe and advanced pulmonary COVID-19 [14]. In addition to the clinical literature, some postmortem CT (PMCT) imaging findings have been reported, though they are not specific or highly suggestive of lung SARS-CoV-2 infection [16][17][18][19][20][21][22][23][24]. As a consequence, PMCT imaging has been proposed as a useful tool for postmortem investigations in diagnosed or suspected cases of SARS-CoV-2 infection to augment the numbers of postmortem examinations, especially in the first wave [25] or more recently as a screening method for SARS-CoV-2 infection before autopsy [16][17][18][19][20][21][22]24].…”
Section: Introductionmentioning
confidence: 99%